Ars predicandi. Wybitni kaznodzieje konwentu kraśnickiego - Pietrzykowski, Jan (Archiwa, Biblioteki i Muzea Kościelne, 2017)
The article presents an outline of the issues connected with the Canons Regular preaching, including the profi les of the most outstanding preachers and the topics covered in their sermons. The study of the achievements of the Canons Regular preachers led to the conclusion that, in comparison with other religious orders boasting the most outstanding preachers in their ranks in Poland, the contribution of the Canons Regular of Lateral in this field is not very impressive. They are not among the well-known defenders of the Catholic faith against the attacks of the dissenters, they are not seen among the chaplains at royal or magnate courts either. In addition, the representatives of this order are noticed quite late among the camp’s preachers who played an important role in the military pastoral care. Nevertheless, preachers from the Cracow congregation of the Canons Regular occupied a prominent place among a large number of male orders in the lands of Poland and Lithuania. They were frequently active outside their own abbey or provostries.